2017
DOI: 10.5130/ajceb.v17i2.5292
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Coherent Theory of Project Alliancing: Discovering the System’s Complex Mechanisms Yielding Value for Money

Abstract: Alliancing is a relatively new construction project delivery method receiving increasing interest globally while also eliciting many questions about its effectiveness. That is why its operating logic should be clarified beyond the currently existing general views. Correspondingly, this paper aims to define the means and mechanisms which influence the capacity of alliancing to produce value for money. The work establishes the interlaced impact chains between formal basic solutions of alliancing and the key resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…While not primarily being about project alliancing, Vilasini et al (2014) developed and evaluated a framework for process improvement in alliance projects. Lahdenperä (2017) aimed to define the means and mechanisms which influence the capacity of alliancing to produce value for money. Sakal (2005) discusses project alliancing as a relational contracting mechanism for dynamic projects.…”
Section: Alliancingmentioning
confidence: 99%
“…While not primarily being about project alliancing, Vilasini et al (2014) developed and evaluated a framework for process improvement in alliance projects. Lahdenperä (2017) aimed to define the means and mechanisms which influence the capacity of alliancing to produce value for money. Sakal (2005) discusses project alliancing as a relational contracting mechanism for dynamic projects.…”
Section: Alliancingmentioning
confidence: 99%
“…One of the key features of project alliances is a focus on collaboration and knowledge integration arrangements among the partners that supports innovative outcomes and behaviors (Manley et al, 2009). By involving the contractor at an early stage of the design process, the alliance will be able to deliver complex product systems with innovative solutions under uncertain conditions (Lahdenperä, 2017). In some projects, only a small percentage of the ideas discovered during the development phase are further prioritized and put into practice due to the fact that some ideas are aimed at unrealistic savings (Alliance executive team, 2018).…”
Section: B4: Rework Decreases Errorsmentioning
confidence: 99%
“…Recent evidence has suggested that project alliances are an effective way to manage and deliver complex projects and to create value in uncertain project contexts (Lahdenperä, 2017;Suprapto et al, 2016). However, the majority of studies have focused on static assessments of the characteristics, practices, outcomes, and benefits of project alliances (Walker and Lloyd-Walker, 2015).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 2 more Smart Citations